(untitled) (International journal of artificial intelligence, 2025)
The article analyzes the causes of poverty of the population, highlights its relevance and impact on economic development. Economic analysis, statistical data and scientific approaches are used to solve the problem. This article is devoted to analyzing the causes of poverty in the world. It considers regional, economic and social factors. Methodological approaches are used to solve the problem. The main factors of poverty, including unemployment, low quality of education and economic inequality, are discussed. Socio-economic measures are proposed.